Solid-State Materials for Opto-Spintronics: Focus on Ferromagnets and 2D Materials - Ana-Maria Florea (Raduta); Stefan Caramizoiu; Ana-Maria Iordache; Stefan-Marian Iordache; Bogdan Bita (Solids)
Opto-spintronics is an emerging field that focuses on harnessing light to manipulate and analyze electron spins to develop next-generation electronic devices. This paper explores recent progress and the role of solid-state materials in opto-spintronics by focusing on key classes of materials, such as ferromagnetic semiconductors, two-dimensional (2D) transition metal dichalcogenides (TMDCs), and topological insulators. It examines the unique properties of ferromagnetic and antiferromagnetic materials and their ability to interact with light to affect spin dynamics, offering potential for improved sensing and quantum computing. By combining opto-spintronics with solid-state systems, spintronic devices could become faster and more efficient, leading to new technological advancements and scalable technologies.